Intensive dysarthria therapy for younger children with cerebral palsy. (26th February 2013) - Pennington, Lindsay; Roelant, Ella; Thompson, Vicki; Robson, Sheila; Steen, Nick; Miller, Nick
Abstract : Aim: The aim of this study was to investigate if intervention targeting breath support, phonation, and speech rate increases speech intelligibility and participation in the conversational interactions of younger children with dysarthria and cerebral palsy (CP). Method: Fifteen children with dysarthria and CP (nine males, six females; age range 5–11y, mean age 8y, SD 2y; CP type: eight spastic, four dyskinetic, one ataxia, two Worster Drought syndrome; Gross Motor Function Classification System levels II–IV, median level II) participated in this study. Children received three sessions of individual therapy per week for 6 weeks. Intelligibility of single words and connected speech was compared across five points: 1 and 6 weeks before therapy and 1, 6, and 12 weeks after therapy. Three familiar listeners and three unfamiliar listeners scored each recording. Participation in communicative interactions was measured using the Focus on the Outcomes of Communication Under Six (FOCUS) tool. Analyses of variance and paired t ‐tests were used to investigate change. Results: Mean speech intelligibility increased after therapy to familiar listeners (single words 10.8%, 95% confidence interval [CI] 7.2–14.4; connected speech 9.4%, 95% CI 4.8–14.1) and unfamiliar listeners (single words 9.3%, 95% CI 6.8–11.8; connected speech 10.5%, 95% CI 7.3–13.8). FOCUS scores increased following therapy for parents (mean increase 30.3, 95% CI 10.2–50.4) and for teachers (28.25, 95% CI 14.4–42.1), but changes did not correlate with intelligibility. A wide variation was seen in individual responses to therapy. Interpretation: Brief intensive therapy is associated with gains in intelligibility and communicative interactions for some younger children with dysarthria. Abstract : This article is commented on by Dykstra on pages 403–404 of this issue.